Particularism Doesn’t Flatten - Hicks, Amelia (Journal of moral philosophy, 2016)
Sean McKeever and Michael Ridge object that moral particularism ‘flattens the moral landscape’, that is, that particularism treats reasons of different kinds as if they were reasons of the same kind. This objection is misguided in two respects. First, particularists need not say that every feature can be a moral reason. Second, even if particularists were committed to saying that every feature can be a moral reason, they would still not be committed to the view that every feature can have direct moral relevance. The failure of this objection shows that the objection exploits side-constraints that need not be placed on moral particularism.